Teoría de las representaciones sociales: la emergencia epistemológica para la educación - Jefferson da Silva Moreira; Eduardo Oliveira Miranda (Universidade Federal de Rondônia, 2019)
The objective of this essay is to present, from a foray into literature, the historical, theoretical and epistemological foundations that culminated in the creation of Theory of Social Representations (TRS) in the mid-1960s in France by Romanian psychologist Serge Moscovici , seeking to establish relations of this theoretical postulate with the field of Education. We base ourselves theoretically on the productions of Moscovici (2007); Jodelet (2001); Abric (2002); Farr (2004); Arruda (2005); Doise (2002), among other researchers, who brought important contributions to the theoretical reflections woven throughout this text. We conclude the reflections betting on the important contribution of the notion of social representations as a subsidy for the configuration of a new educational paradigm that destabilizes the hierarchizations between the knowledge historically conceived as scientific and the knowledge of common sense, between popular knowledge and scholarly knowledge. In this sense, we bet on the emergence of the design of a new epistemological and paradigmatic principle for the field of Education, which encompasses different knowledge from the perspective of the ecology of knowledge.